2019
DOI: 10.1002/ejp.1474
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for episodes of back pain in emerging adults. A systematic review

Abstract: Background and Objective The transition from adolescence to adulthood is a sensitive period in life for health outcomes, including back pain. The objective was to synthesize evidence on risk factors for new episodes of back pain in emerging adults (18–29 years). Methods The protocol was registered in PROSPERO (CRD42016046635). We searched Medline; EMBASE; AMED and other databases up to September 2018 for prospective cohort studies that estimated the association between risk factor(s) and self‐reported back pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 90 publications
3
18
0
2
Order By: Relevance
“…This emphasises not only the individual suffering but also the high healthcare burden for society. These individuals also have an increased risk of later persistent pain (Beltramini et al, ; Hassett et al, ; Hestbaek, Leboeuf‐Yde, & Kyvik, ; Hestbaek, Leboeuf‐Yde, Kyvik, & Manniche, ; Jones, Silman, Power, & Macfarlane, ; Oiestad et al, ) and health impairments (Hoftun et al, ; Huguet & Miro, ; Kamper et al, ; Roth‐Isigkeit et al, ), as well as difficulties with school performance (Grimby‐Ekman et al, ; Groenewald et al, ; O'Sullivan, Beales, Smith, & Straker, ; Petersen, Hagglof, & Bergstrom, ).…”
Section: Discussionmentioning
confidence: 99%
“…This emphasises not only the individual suffering but also the high healthcare burden for society. These individuals also have an increased risk of later persistent pain (Beltramini et al, ; Hassett et al, ; Hestbaek, Leboeuf‐Yde, & Kyvik, ; Hestbaek, Leboeuf‐Yde, Kyvik, & Manniche, ; Jones, Silman, Power, & Macfarlane, ; Oiestad et al, ) and health impairments (Hoftun et al, ; Huguet & Miro, ; Kamper et al, ; Roth‐Isigkeit et al, ), as well as difficulties with school performance (Grimby‐Ekman et al, ; Groenewald et al, ; O'Sullivan, Beales, Smith, & Straker, ; Petersen, Hagglof, & Bergstrom, ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Other significant risk factors associated with LBP include smoking and occupational hazards such as heavy lifting and poor posture. 20,21 However, prevalence estimates of LBP in older adults vastly differ due to the lack of a standard definition of LBP and variations in sampling and experimental methods as reported by clinical and administrative studies. 22 Authors of these studies also provide limited information regarding location and severity of pain, as well as LBP-induced limitations on normal functioning.…”
Section: Prevalence Of Lbp and Ldhmentioning
confidence: 99%
“…when it is associated with a sports‐related injury), it may also become chronic and persistent 2 . Previous research on musculoskeletal pain in adolescence, which has primarily focused on back pain, 2,3 has shown that pain during adolescence is an important predictor of future pain 4–6 . It can negatively impact everyday activities such as school attendance, 7 sleep, 7 social functioning, 8 withdrawal from social and sports activities, 8,9 and reduced physical activity, 10 which in itself is a risk factor for obesity and diabetes 11…”
Section: Introductionmentioning
confidence: 99%